Mesin Roll Pelat Bahan Pewter - Rodika Rodika; Agung Supriyadi; Indra Anggriawan; Sutiryo Sutiryo (Manutech : Jurnal Teknologi Manufaktur, 2016)
The design of the machine roll plate made from pewter to be developed is a machine that is simple, easy to be usde and does not endanger the user and use 1 phase ac motors. The system uses two cylinder rolls at the top and bottom with a thickness regulator by using a screw system. The material used is steel st. 40 for the roll materials and to get the smooth rolling process, then roll grinding cylinder. For the power cylinder roll will be analyzed by the software that is to know the voltage that occurs in the cylinder roll when rolling the pewter plate by assumed load of 1000 kg. The result of this research is the engine may roll the plate pewter with a size of 260 mm x 70 mm x 3 mm to a size of 430 mm x 77 mm x 1 mm, which takes 6 minutes of 1 plate pewter, plate surface pewter solid and smooth, and the size of the plate length increases ± 98% and ± 7% width, thus saving time, effort and cost in the casting process.